Competence-based Education. A Reflexive Approach from the Theory - Maria Aurelia San Juan Bosch; Rubén Darío García Núñez; Raúl Alpizar Fernandez; Roberto Baños García; Roberto Morales Ojeda; Barbara Jiménez Hernández (Medisur)
Background: in present times, competences seem to be a conceptualization and an action mode in human resources management, allowing a better coordination between management, work and education. As part of a systematic vision and organization, competences have even been expressed as a certification system legally established in several countries. Objective: to reflect on the need to develop competence-centered education, in order to integrate all knowledge that enables the general formation of students. Conclusion: the competence approach in education can be considered as a tool to provide an action mode and a common language for the training of human resources in tertiary education.